Characteristics of Klawoguk Watershed In Sorong City, Southwest Papua - Mahmud; Wijaya, Danang Jatmika Wahyu; Wahyudi; Nugroho, Bambang; Dwiranti, Febriza; Mutakim (Jurnal Ilmu Tanah dan Lingkungan, 2024)
Floods have become the biggest disaster in the last decade. This study aims to examine the characteristics of the Klawoguk Watershed which are expected to contribute in planning, managing and mitigating floods in Sorong City. This study used survey methods, spatial analysis and field observations. The results showed that the characteristics of the Klawoguk watershed have a very wet tropical climate type with rainfall throughout the year without a recognized dry season. In an oval-shaped watershed, it is possible for the water to take longer to reach the water’s end point. The flat topography covering an area of ​​2,599.30 ha has become the urban area of ​​Southwest Papua Province including the villages of Sawagumu, Malaingkedi, Klasabi, Kalwalu and Klamana which are prone to flooding. In the last seven months the flow regime coefficient (CRF) has been changing, dominated by very low, which means that the water flow in the Klawoguk river is more stable. The sediment is dominated by very high podzolic soil types and there is degradation of protected forest by taking soil and C excavation which causes an increase in sediment yield in rivers.